Evaluation of Occupational Safety and Health Risks in Steel Construction Work in E-House Projects in the Modern Steel Construction Industry - Ananda Doharman Sormin; Hery Irwan (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
The modern steel construction industry presents a relatively high level of Occupational Safety and Health (OSH) risk due to work-at-height activities, heavy material lifting, welding, steel cutting, and heavy equipment operation. E-House projects, as modular steel-based facilities, involve complex construction activities requiring comprehensive risk evaluation. This study aims to evaluate OSH risks in steel construction work on E-House projects using the Hazard Identification, Risk Assessment and Risk Control (HIRARC) approach integrated with Job Safety Analysis (JSA). A quantitative descriptive design was employed through field observations, interviews, documentation studies, and risk assessments covering fabrication, lifting, erection, welding, grinding, and work-at-height activities. The findings identified 35 potential hazards consisting of 8 high-risk, 19 medium-risk, and 8 low-risk categories. The highest risks were associated with steel erection, crane lifting operations, and work-at-height activities with risk ratings exceeding 15. Risk control measures including personal protective equipment, permit-to-work systems, equipment inspections, safety briefings, and supervision significantly reduced risk levels. The study contributes to the enhancement of OSH management systems in modern steel construction projects and provides practical references for improving workplace safety culture.